Improving DSSS signal PN code phase measurement precision by 3-points quadratic interpolation - GONG Guo-hui; LI Si-kun (Tongxin xuebao)
A method using 3-points quadratic interpolation to process correlation spectrum peak data was proposed to improve precision of DSSS signal PN code phase measurement.The method used data points around correlation spec-trum peak to determine a quadratic interpolation function,then located the maximum point of the function so as to deter-mine the precise position of correlation spectrum peak,thus effectively increased the precision of measurement.Experi-ments show that the method reaches the goal of greatly increasing the precision of DSSS signal PN code phase measure-ment.